Protective Effects of Hydroxychloroquine against Accelerated Atherosclerosis in Systemic Lupus Erythematosus - Alberto Floris; Matteo Piga; Arduino Aleksander Mangoni; Alessandra Bortoluzzi; Gian Luca Erre; Alberto Cauli (Mediators of Inflammation)
Cardiovascular (CV) morbidity and mortality are a challenge in management of patients with systemic lupus erythematosus (SLE). Higher risk of CV disease in SLE patients is mostly related to accelerated atherosclerosis. Nevertheless, high prevalence of traditional cardiovascular risk factors in SLE patients does not fully explain the increased CV risk. Despite the pathological bases of accelerated atherosclerosis are not fully understood, it is thought that this process is driven by the complex interplay between SLE and atherosclerosis pathogenesis. Hydroxychloroquine (HCQ) is a cornerstone in treatment of SLE patients and has been thought to exert a broad spectrum of beneficial effects on disease activity, prevention of damage accrual, and mortality. Furthermore, HCQ is thought to protect against accelerated atherosclerosis targeting toll-like receptor signaling, cytokine production, T-cell and monocyte activation, oxidative stress, and endothelial dysfunction. HCQ was also described to have beneficial effects on traditional CV risk factors, such as dyslipidemia and diabetes. In conclusion, despite lacking randomized controlled trials unambiguously proving the protection of HCQ against accelerated atherosclerosis and incidence of CV events in SLE patients, evidence analyzed in this review is in favor of its beneficial effect.